ANALISIS PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN PADA MNC PLAY JAKARTA - Sri Lestari (CKI ON SPOT, 2018)
The study analyzed the influence of price and service quality on customers’ satisfaction and its effect on their loyalty. The object of the study was MNC Play Jakarta.. The objective of the study was to analyze and to know the direct influence of price, service quality, and customers’ satisfaction on customers’ loyalty. Besides theoretical model, the study also formulated three hypotheses. Purposive sampling method had been selected to obtain the data in this study. The samples comprised 190 respondents who were the customers of MNC Play Jakarta. The data were analyzed by using Structural Equation Model with Amos computer program. The result of the study showed that price did not have any direct influence on customers’ satisfaction. Service quality had direct influence on customers’ satisfaction which, in turn, had direct influence on customers’ loyalty.